PENDAMPINGAN PENYUSUNAN RENCANA KERJA (RENJA) PADA PEMERINTAHAN DAN OTONOMI DAERAH PROVINSI KALIMANTAN TENGAH - Nadya Tiara Cindi; Jhon Lis Berger; Golda Belladonna Umbing; Adila Durrotul Ghina (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
The Bureau of Governance and Regional Autonomy (Biro Pemerintahan dan OTDA) of the Regional Secretariat of Central Kalimantan Province faces complex administrative challenges in managing and verifying Regional Work Plan (RENJA) documents from multiple regional agencies (OPD). Limited administrative human resources, intricate verification requirements based on Permendagri No. 86 Tahun 2017 and Kepmendagri 050-5889, and the high volume of planning documents requiring meticulous checking create significant administrative burdens for the bureau. This community service activity aimed to provide administrative assistance to the Bureau's Administration Unit (Bagian Tata Usaha) in managing, verifying, and archiving RENJA-related documents, conducted from January 22 to May 22, 2026. The author applied participatory administrative assistance, administrative observation, and experiential learning approaches through four stages: observation, administrative assistance, document verification, and evaluation. The results demonstrate that structured administrative assistance contributes meaningfully to the efficiency and quality of RENJA document management in regional government bureaus.